SISTEM PENDUKUNG KEPUTUSAN MENENTUKAN OBAT DIABETES TERBAIK MENGGUNAKAN METODE TOPSIS - Melati Sitinjak; Suhada Suhada; Rafiqa Dewi (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
Diabetes mellitus or diabetes, occurs due to reduced production of the hormone insulin which functions to convert sugar into energy, and convert excess sugar levels in the body into fat. This condition results in the occurrence of hyperglycemia which transmits glucose in the urine. The more complex causes of diabetes are due to heredity, environmental factors include age, obesity, insulin resistance, physical activity, and unhealthy lifestyle of patients also play a role in the occurrence of diabetes. The purpose of this study is to produce a decision making system to determine diabetes medications best using the topsis method. The Topsis method is used to take the best alternative solution by paying attention to the shortest distance from the positive ideal solution and the farthest distance from the negative solution, in determining the best diabetes drug based on predetermined criteria, so that it can be recommended as the next decision support system. The results of the application of the TOPSIS method can produce output in the form of ranking of diabetes drugs and determine diabetes drugs that have the highest preference value among other alternatives. The criteria used to determine the best diabetes drugs are 5, namely: Drug Efficacy, Drug Indications, Side Effects, Drug Prices, Drug Guarantees. This application was built using web programming language and Mysql database.Keywords: Decision support system, Diabetes Medication, TOPSIS, Web, MySql